2003
DOI: 10.1080/00102200302384
|View full text |Cite
|
Sign up to set email alerts
|

Combustion dynamics of an acoustically forced flame

Abstract: A technique has been devised that can provide information about the local dynamic response of a flame to an acoustic field. In the experiments, a flame in an acoustic chamber is subjected to pressure oscillations by a pair of lowfrequency drivers. The response of the flame is visualized by planar laserinduced fluorescence of the hydroxyl radical, which is used as a qualitative indicator for heat release in the flame. The resulting images are phase-resolved and averaged to yield a qualitative picture of the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Recent advancements in measurement methods [2,3,18,23,27,33,39,40] and the improved understanding of various phenomena underlying this complex problem have increased the prediction capability [15,25]. However, the prediction methods greatly depend on the knowledge of the response of the flame to prescribed conditions, information that might be obtained from experiments [3,5,10,22] or modelling [1,6,15,25,31,42].…”
Section: Introductionmentioning
confidence: 98%
“…Recent advancements in measurement methods [2,3,18,23,27,33,39,40] and the improved understanding of various phenomena underlying this complex problem have increased the prediction capability [15,25]. However, the prediction methods greatly depend on the knowledge of the response of the flame to prescribed conditions, information that might be obtained from experiments [3,5,10,22] or modelling [1,6,15,25,31,42].…”
Section: Introductionmentioning
confidence: 98%
“…A similar approach is recently reported by Pun et al [32]. To examine the contribution of the fluctuations in the flame area to the total heat release rate fluctuations, a threshold intensity level is set in all the high-speed chemiluminescence images based on the intensity distribution in the unperturbed flame.…”
Section: Methodsmentioning
confidence: 96%
“…This work also examines the link between flame behavior and mixing behavior. The current effort builds on previous work [13] by focusing on the fuel-air structure upstream of the flame front. To this end, two-dimensional images of the fuel-air distribution are obtained by imaging the acetone concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Culick [10,11] developed a theory that is based on the Rayleigh index. The coupled effects of acoustic forcing and combustion heat release on species concentration inside the flame zone were examined by Pun et al [12,13] using OH-PLIF and chemiluminescence. This revealed that in the flame region the response of the combustion process under acoustic excitation is strongly phase-dependent, and this dependence was quantified.…”
Section: Introductionmentioning
confidence: 99%